Stabilizing effects in temporal fluctuations: management, traits, and species richness in high-diversity communities - Lepš, Jan; Májeková, Maria; Vítová, Alena; Doležal, Jiří; de Bello, Francesco (Ecology, 2018)
The loss of biodiversity is thought to have adverse effects on multiple ecosystem functions, including the decline of community stability. Decreased diversity reduces the strength of the portfolio effect, a mechanism stabilizing community temporal fluctuations. Community stability is also expected to decrease with greater variability in individual species populations and with synchrony of their fluctuations. In semi-natural meadows, eutrophication is one of the most important drivers of diversity decline; it is expected to increase species fluctuations and synchrony among them, all effects leading to lower community stability. With a 16-year time series of biomass data from a temperate species-rich meadow with fertilization and removal of the dominant species, we assessed population biomass temporal (co)variation under different management types and competition intensity, and in relation to species functional traits and to species diversity. Whereas the effect of dominant removal was relatively small (with a tendency toward lower stability), fertilization markedly decreased community stability (i.e., increased coefficient of variation in the total biomass) and species diversity. On average, the fluctuations of individual populations were mutually independent, with a slight tendency toward synchrony in unfertilized plots, and a tendency toward compensatory dynamics in fertilized plots and no effects of removal. The marked decrease of synchrony with fertilization, contrary to the majority of the results reported previously, follows the predictions of increased compensatory dynamics with increased asymmetric competition for light in a more productive environment. Synchrony increased also with species functional similarity stressing the importance of shared ecological strategies in driving similar species responses to weather fluctuations. As expected, the decrease of temporal stability of total biomass was mainly related to the decrease of species richness, with its effect remaining significant also after accounting for fertilization. The weakening of the portfolio effect with species richness decline is a crucial driver of community destabilization. However, the positive effect of species richness on temporal stability of total biomass was not due to increased compensatory dynamics, since synchrony increased with species richness. This shows that the negative effect of eutrophication on community stability does not operate through increasing synchrony, but through the reduction of diversity.
Keywords: Biodiversity; biomasa; ekosystém; biodiverzita; Ecology; ekologie; eutrofizace; Eutrophication; Ecosystem; Biomass